The study of correlation of quality of life assessment with visual function among Kelantan glaucomatous patients - Azreen Redzal, Anuar (2008)
Objective approaches of measuring the visual function impairment such as visual field and visual acuity are inadequate and do not totally reflects the true quality of lite in the glaucoma patients. Currently. questionnaires are used as the health related quality of life instruments. Only few studies has been done to assess the correlation between the two. Objective: To evaluate the reliability of the modified NEI VFQ 25 in the Kelantan glaucomatous patients and to correlate the modified NEI VFQ 25 and utility analysis to the visual field and visual acuity impairment. Methods: A cross sectional study was carried out from April to October 2006. Translation of the questionnaires by translation and back translation method was carried out first. f()llmved by a pilot study on 30 glaucoma patients using the translated questionnaires. The process or reliability assessment on the questionnaires were done after the pilot study. There were 134 patients selected for the study. Ocular examination was carried out on the patients including the visual acuity assessment using the standard Snellen chart. After completion of the ocular examination, the patients underwent an interview by in person approach using the modified NEI VFQ 25 and utility analysis questionnaire. Lastly, the patients underwent the Esterman binocular visual field test usmg standard Carl Zeiss Humphrey Perimetry machine. Results: Cronbach's a for the modified NEI VFQ 25 was 0.740, indicating moderate internal consistency. The total modified NEI VFQ 25 showed significant positive correlation with Esterman binocular visual field (P<O.OO 1 ). A significant negative correlation noted between modified NEI VFQ 25 score with LogMAR visual acuity in the better eye (P=0.009) and also with LogMAR visual acuity in the worse eye (P<0.001 ). Modified NEI VFQ 25 subscale showed higher correlation with the visual acuity in worse eye compared to better eye. Modified NEI VFQ 25 subscale showed low to strong correlation with Esterman binocular visual field. A significant negative correlation was noted bctw·een modified utility analysis with LogMAR visual acuity in the better eye (P=O.O l 0) and also with LogMAR visual acuity in the worse eye (P<O.OO 1 ). A significant positive correlation was noted between modified utility analysis with Esterman binocular visual field (P<O.OO I). Conclusion: The validity and reliability of the modified NEI VFQ 25 were shown to be sufficient. This questionnaire is applicable to the Malay-speaking population as quality of life instrument.A significant correlation noted between modified NEI VFQ 25 with visual field and visual acuity of glaucoma patients. The modified utility analysis also showed significant correlation with visual field and visual acuity of glaucoma patients.